Numerical study on the energy performance of an axial-flow pump with different wall roughness - Chen, Yuling; Sun, Qing; Li, Zhixiang; Gong, Yan; Zhai, Jianwei; Chen, Huixiang (Frontiers in Energy Research, 2022)
Pumping stations play an important role in China’s South-to-North Water Diversion, agricultural irrigation, and municipal drainage. Some pumping station units have been put into operation for long periods with improper operation and require maintenance. Moreover, the surfaces of the flow components have been worn and corroded, leading to an increase in the relative roughness and a decrease in the hydraulic performance efficiencies of pumping station units. In this work, we performed field measurements and numerical simulations to study the influence of the wall roughness on the hydraulic performance of slanted axial-flow pump devices under multiple working conditions. The effects of the wall roughness of the impeller chamber on the hydraulic performance of the pump, the guide vane chamber, and the inlet and outlet flow channel were investigated. Wall roughness had the largest influence on the hydraulic performance of the pump and the smallest influence on the inlet and outlet flow channels. For devices with different roughness values on the impeller chamber wall under different flow rate conditions, the performance of the pump device worsened under the large-flow-rate condition, and the device performance was better under the small-flow-rate and designed flow conditions. The efficiency of the slanted axial-flow pump device decreased significantly as the flow rate increased. Under the same flow rate condition, the performance of the device with Ra = 5 μm was similar to that with a smooth wall, where Ra is the roughness of the wall. With the increase in the roughness, the uniformity of the axial velocity distribution coefficient decreased, and the velocity-weighted average drift angle increased. External characteristic parameters, such as the torque and the static pressure, on the blade pressure surface gradually decreased with the increase in the wall roughness. A large roughness could induce instability of the wall flow and enhance the turbulent kinetic energy near the blade surface.